CD68 AND STABILIN-1 POSITIVE MACROPHAGES IN POSTINFARCTION MYOCARDIAL REGENERATION - A. E. Gombozhapova; Yu. V. Rogovskaya; М. S. Rebenkova; Yu. G. Kzhyshkovskaya; V. V. Ryabov (Российский кардиологический журнал)
Aim. Translation of experimental data on cardiac macrophages populations in postinfarction cardiac regeneration, into clinical practice.Material and methods. In the study, 41 patients included, with fatal myocardial infarction (MI) type 1. All patients were selected to 4 groups according to fatal outcome timing. Together with routine pathohistology, immune histochemistry was done, on macrophageal infiltration. As the markers of macrophagal line we used CD68; stabilin-1 was used for M2 macrophages.Results. The amount of CD68+ and stabilin-1+ macrophages in infarction zone increased and reached the peak in regeneratory phase, and did not decline at later stage. In peri-infarction area the amount of CD68+ macrophages increased during inflammatory phase, reached peak at reparation phase and did not change anymore either. By the results of multiple regression, the model was proposed, showing interrelations between the grade of macrophage infiltration and clinical markers of MI course.Conclusion. Our study translates experimental results on cardiac macrophages subpopulations in postinfarction cardiac regeneration into clinical area. We observed a biphasic response of cardiac macrophages on acute ischemia, similar of that in mice. The grade stabilin-1+ macrophagal infiltration intensity increased at regeneration phase. There was significant strong positive correlation of the numbers of stabilin1+ macrophages and MI course phase, that underlies potential application of stabilin-1 as diagnostic biomarker of M2 macrophages in MI patients.